2021
DOI: 10.3390/pharmaceutics13091354
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Tailored Zein Nanoparticles: Strategies and Applications

Abstract: Plant-derived proteins have emerged as leading candidates in several drug and food delivery applications in diverse pharmaceutical designs. Zein is considered one of the primary plant proteins obtained from maize, and is well known for its biocompatibility and safety in biomedical fields. The ability of zein to carry various pharmaceutically active substances (PAS) position it as a valuable contender for several in vitro and in vivo applications. The unique structure and possibility of surface covering with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 141 publications
(193 reference statements)
0
24
0
Order By: Relevance
“…Namely, it offers greater bioavailability, protection, and prolonged, controlled, and more effective release of incorporated substances at the target site. Many therapeutic agents have been successfully loaded into zein-based nanoparticles, e.g., doxorubicin, heparin, 5-fluorouracil, coumarin, quercetin, resveratrol, vitamin D3, and different antimicrobials [ 185 , 192 , 193 , 194 ].…”
Section: Plant-based Biopolymeric Nanoparticles Used For Healthcare A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, it offers greater bioavailability, protection, and prolonged, controlled, and more effective release of incorporated substances at the target site. Many therapeutic agents have been successfully loaded into zein-based nanoparticles, e.g., doxorubicin, heparin, 5-fluorouracil, coumarin, quercetin, resveratrol, vitamin D3, and different antimicrobials [ 185 , 192 , 193 , 194 ].…”
Section: Plant-based Biopolymeric Nanoparticles Used For Healthcare A...mentioning
confidence: 99%
“…The prepared spherical nanoparticles with a diameter of about 120 nm showed excellent cellular uptake by C6 glioma cells and the ability to penetrate 3D tumor spheroids. Zein is also widely used in tissue engineering [ 192 ]. Hadavi et al [ 196 ] synthesized zein nanoparticles as a delivery system for a bone morphogenic protein-6 (BMP6) derived peptide using a liquid–liquid phase separation method.…”
Section: Plant-based Biopolymeric Nanoparticles Used For Healthcare A...mentioning
confidence: 99%
“…The physical modification method can select materials with specific properties (pH response, magnetism, temperature sensitivity, etc.,) and zein solution to form a nanocomposite carrier so that the nanocarriers can quickly release active substances under specific pH, external magnetic field, and different temperature responses [ 82 ]. In addition, chemical modification can obtain some additional properties by changing the chemical groups of zein, mainly including liver protection activity, pH responsiveness, and targeting, among others [ 83 ].…”
Section: Application Of Bioactive Substances Loaded On Plant Protein-...mentioning
confidence: 99%
“…However, a significant barrier in successful drug delivery is the blood-brain barrier (BBB) that bypasses the chemotherapeutics' intratumoral delivery [153]. Zein is currently important because of its safety, biodegradation capabilities, and sustained drug release characteristics [154]. Novel research indicated that surface functionalization of zein NPs with polydopamine (PD) layers resulted in enhanced solubility, biocompatibility, stability, and flexibility for attachment of various biological functional groups.…”
Section: Polydopamine-layered Zein Nanocarriersmentioning
confidence: 99%